SEDENTARY AND DYNAMIC ACTIVITIES OF ADOLESCENTS AS PREDICTIONS OF POSTURAL STATUS - Laštro, Dijana; Pilipović-Spasojević, Olivera (Medicinski časopis, 2018)
Apstrakt Uvod/Cilj. Držanje tijela je navika motornih aktivnosti nadograđena na određenu morfološku i funkcionalnu osnovu. U periodu rasta i razvoja adolescenta, sedentarne navike i fizička aktivnost su bitni faktori držanja tijela. Cilj ovog rada je bio da se ustanovi koja vrsta aktivnosti sedentarna, dinamička ili obe ove aktivnosti imaju uticaj na držanja tijela kod djece starijeg osnovnoškolskog uzrasta. Metode. Urađena je prospektivna studija sa 120 ispitanika grupisanih u tri grupe, uzrasta od 10 do 16 godina sa jednakim učešćem pripadnika oba pola. Prvu grupu čini 40 djece koja se aktivno bave sportom. Drugu grupu čini 40 djece koja se aktivno ne bave sportom, a treću grupu 40 djece koja imaju deformitet kičmenog stuba. Za potrebe istraživanja koristili smo autorizovani Test za ocjenu držanja tijela (TDT), Test procjene stepena fizičke aktivnosti za djecu školskog uzrasta (TFA) i Body mass index (BMI). Rezultati. U odnosu na svaki kategorički definisani uzorak, ocjenu odličnog držanja tijela nije imalo niti jedno dijete. U prvoj grupi, ocjenu vrlo dobrog i dobrog držanja je imalo 77,5 %, druga grupa 50% a treća 35% djece. Ustanovljena je statistička značajnost između držanja tijela posmatranih grupa, dinamičkih aktivnosti (p=0,000) i TFA ukupnog skora (p=0,000), što nije bilo slučaj sa sedentarnim aktivnostima (p=0,315). Zaključak. Suprotno od očekivanog, rezultati su pokazali da su dinamičke aktivnosti imale važniji uticaj na držanje tijela za svaki kategorički definisani uzorak u odnosu na sedentarne aktivnosti. Potrebne su hitne intervencije koje imaju za cilj da promovišu fizičku aktivnost među adolescentima kroz razvoj preventivne zdravstvene politike. Ključne riječi: držanje tijela, sedentarne i dinamičke aktivnosti, adolescenti Abstract Introduction/Aim. Body posture is a habit of motor skills upgraded to specific morphological and functional base. During the period of adolescent’s growth and development, sedentary habits and physical activity are important factors of body posture. The aim of this work was to find out which type of activity, sedentary, dynamic or both, influence the body posture of senior elementary school children. Methods. This prospective study involved 120 examinees aged 10 to 16 of both genders, divided into three groups. The first group consisted of 40 sport active children. The second group consisted of 40 non-sport active children, and the third group of 40 children who had a deformity of spine. The authorized test for body posture, Physical Activity Evaluation Test for elementary school children (TFA) and Body Mass Index (BMI) were used. Results. Excellent body posture had none of the children. Very good and good body posture grade had 77.5 %, 50% and 35% of children in groups 1, 2 and 3, respectively. Significant correlation has been established between the body posture of the monitored groups on one side and the dynamic activities (p=0.000), and TFA on the other (p=0,000), which was not the case with the sedentary activities (p=0.315). Conclusion. Contrary to the expected, the results showed that the dynamic activities had more important influence on body posture in each category of children, when compared to sedentary activities. Urgent interventions in preventive health policy are needed to promote physical activity among adolescents. Key words: body posture, sedentary and dynamic activities, adolescents